Pengaruh Upah Kerja, Beban Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan Pada UMKM Bakpia Latief - Solikhah, Solikhah; Listyani, Indah; Wahyudi, M. Adi Trisna (FEB Universitas Maritim Semarang, 2025)
This study aims to analyze the effect of wages, workload, and work discipline on employee performance at Bakpia Latief MSME in Kediri. The research method employed is quantitative with a survey technique. The sample consists of 32 respondents selected through a saturated sampling technique. Primary data were collected using a Likert-scale questionnaire that had been tested for validity and reliability, while secondary data were obtained from documentation and literature review. Data analysis was conducted using multiple linear regression preceded by classical assumption tests. The results indicate that wages have a positive and significant effect on employee performance, while workload and work discipline do not have significant partial effects. However, simultaneously, the three independent variables significantly influence employee performance, with a coefficient of determination (R²) of 0.579, indicating that 57.9% of employee performance variation can be explained by wages, workload, and work discipline. This study highlights the importance of a fair wage policy in enhancing performance, although other factors such as workload and discipline still need to be managed proportionally.